O movimento brasileiro de alfabetização no cenário santista da educação de jovens e adultos -1970-1984 - Monteiro, Thalita Di Bella Costa (2014)
The Brazilian Literacy Movement (MOBRAL), the exception´s government program for adult and young adult education, who commanded the country between 1964 and 1985, was an initiative to solve the illiteracy of the Brazilian population. The program´s structure privileged local performance and the object of this research is to find out how the movement had been installed in Santos, which is far 80km from the principal city and is the most important gateway to export agriculture and industrial products. Because of the National Security Area, during the movement install the population of the city was prohibited to choose own major, in 1969. The settlement of MOBRAL in Santos, apparently, would work automatically because of close relationship between the man who was chosen by military government to lead the city and the president. However, Education Municipal Department documents presents resistance to implement the initiative, beyond it had been denied until the new major and all the secretaries enjoin the city in 1974. Understanding the historical investigation depends on all elements to produce material that under science analysis will have singular results (VEYNE, 1983; GINZBURG, 1989; CHARTIER, 1991; CERTEAU, 2002; LE GOFF, 2003) the present research focus about MOBRAL in Santos city between 1970 and 1984 and was made with law-making documents and officials documents and interviews about how was the initiative´s implement in the city which is relevant to country´s development and is the most important gateway to the produced wealth through the sea.